2020
DOI: 10.1186/s13028-020-00562-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age when group housed and other management factors on playing and non-nutritive sucking behaviour in dairy calves: a cross sectional observational study

Abstract: Background The aim of this study was to investigate if calves’ play behaviour and non-nutritive sucking behaviour, as indirect measures of welfare status, are associated with the age of the calf when group housed, age when observed, age difference within the group, pen size, milk feeding system, current or previous sicknesses, access to dry teat, indoor/outdoor rearing, sex, organic/conventional farm, group size and regrouping events. An observational study was conducted on 176 Danish dairy cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Depending on the protocol, the calves may suffer from hunger or frustration, which would worsen animal welfare at affective states or cognitive judgment and natural living spheres. In order to know whether the animals are hungry, non-nutritive oral behaviors ( 87 , 88 ), cross-sucking ( 89 ) and vocalizations ( 90 , 91 ) could be studied. In addition, when animals do not feel hungry, they engage in more locomotor play, which is a positive indicator of welfare ( 82 , 85 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the protocol, the calves may suffer from hunger or frustration, which would worsen animal welfare at affective states or cognitive judgment and natural living spheres. In order to know whether the animals are hungry, non-nutritive oral behaviors ( 87 , 88 ), cross-sucking ( 89 ) and vocalizations ( 90 , 91 ) could be studied. In addition, when animals do not feel hungry, they engage in more locomotor play, which is a positive indicator of welfare ( 82 , 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another option is to use bottles with nipples, which are more compatible with the natural living sphere. With this method, animals show less non-nutritive sucking ( 88 ). In addition, throughout the literature reviewed, the method of feeding has been modernized with the introduction of automatic milk feeders, which are introduced to animals at around 5 days of age and can be housed in groups of 10–15 calves ( 93 , 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…Veal calves offered milk in a bucket showed more tongue rolling than calves offered milk in an automatic milk feeder (AMF) (Webb et al., 2015 ). Results of a cross‐sectional study in dairy farms also indicated that non‐nutritive sucking behaviour decreased when milk was provided with a teat compared with no teat (via bowl or trough) (Reipurth et al., 2020 ).…”
Section: Assessmentmentioning
confidence: 99%